Lessons Learned: Teaching In-Person During the COVID-19 Pandemic - Tran, Alvin; Kerkstra, Robin L.; Gardocki, Sarah Logan; Papuga, Savannah C. (Frontiers in Education, 2021)
For the Fall 2020 semester, the University of New Haven joined over a third of colleges and universities across the country in offering in-person courses and reopening its campus. Allowing the campus community to safely return was a challenging endeavor, particularly for those at the University’s School of Health Sciences, which offers both non-clinical and clinical courses. In order to create learning environments that adhered to continuously-changing guidelines, our team at the School of Health Sciences was forced to develop and implement innovative strategies. In this article, we share our experiences in fulfilling our roles as faculty, staff, and students at a School of Health Sciences offering in-person, non-clinical and clinical courses during the COVID-19 pandemic. We reflect upon our challenges and share the lessons learned, which we hope will serve as guidance for our collective community in higher education, including those working within schools of public health and health sciences. Our lessons learned are presented in following three themes: 1) preparation for in-person classes; 2) the emotional state of faculty, staff, and students; and 3) innovative practices. Should colleges and universities ever find themselves in similar, yet unprecedented times, our lessons and recommendations may serve as a starting point to assist them in navigating through such tumultuous moments.